(untitled) (KMC Journal, 2025)
This study explores age, gender and provincial differences in labour market outcomes in Nepal with the objective of analyzing the socio-economic determinants of employment and labour force population. These differences are essential to grasp for equal employment opportunity policies and solving workforce issues. Descriptive analysis, analyses of variance (ANOVA) and regression models are employed to measure inequities using data extracted from the Nepal living standard survey 2022/23. Studies reveal employment levels for the 25-44 and 45-64 age groups and reveal poor outcomes for the youth (15-24) and elderly (65+). Currently, young people remain unemployed at a rate of 22.7 percent with low people being engaged in the labour force. Sudurpaschim region’s labour force participation rate is 44.9 percent and negative unemployment rate while in Karnali it is 44.8 percent and Karnali has a slightly higher unemployment rate. The labour in the current society remains gender segregated with women being engaged more in unpaid work in the domestic and farming activities while men are engaged in paid activities in the non-farming activities. Of policy implications, the type of views is advocacy in matters to do with unemployment particularly the youth, regional economics, and gender through education and vocational training. The given figure shows the distribution of investment across different advantaged provinces where special efforts are needed to address the employment disparities and integrate more populace in Nepal. Therefore, this study yields wonderful insights for future policy-based intervention within the labour market.Gender inequality,